Enforcement of capital punishment: legal issues in eliminating drug trafficking / Nasreen Miza Hilmy Nasrijal and Ekmil Krisnawati Erlen Joni - Miza Hilmy Nasrijal, Nasreen; Erlen Joni, Ekmil Krisnawati (Penerbit UiTM (UiTM Press), 2016)
Drug trafficking in Malaysia is punishable with a mandatory capital punishment. To convict a person for drug trafficking is a laborious task for the prosecution. This paper presents the findings of the research on drug trafficking cases which revealed that the courts have been vigorous in meting out capital punishment. However, there are challenges faced by the prosecution in succeeding in cases. This study found various hindrances that frustrate the efforts in combating drug trafficking activities. In some cases, due to evidential procedures and requirements, the person accused for drug trafficking had to be acquitted even though the amount of drugs involved in the case appeared to suggest that there was some drug-related activities. Therefore, while capital punishment is theoretically aimed at deterring drug trafficking, much has to be done to achieve the intended objective.